LDR dan Kredit Terhadap NPL Dimasa Pandemi Covid-19 - Ni Nyoman Juli Nuryani (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
This research aims to find outconsequence of LDR and credit disbursed on NPL thru the Covid-19 pandemic at PT. BPR Indra Candra Singaraja. The analysis method used in this study is multiple linear regression, classical assumption test, determination analysis, f-test and t-test.The outcomes showed that the loan to deposit ratio had an effect on non-performingloans at PT. BPR Indra Candra Singaraja of 0.088 units or -26.8% with the outcomes of hypothesis testing with the t-test, it was found that t-count > t-table (2.086 > 1.688). The effect of the disbursed credit has an effect on non-performingloans at PT. BPR Indra Candra Singaraja is -0.030 units or 68% with the outcomes of hypothesis testing with the T-Test test, it is found that t-count > t-table (3.719 > 1.688) and based on the outcomes of the f test it is known that the effect of loan to deposit ratio and credit distributed to non-performingloans at PT. BPR Indra Candra Singaraja with the results of hypothesis testing with the F-Test test, it was found that f-count > f-table (11.575 > 3.26) with a significant level of 0.00 <0.05.